The Association Between PLAYfun and Physical Activity: A Convergent Validation Study. Issue 2 (2nd April 2020) - Bremer, Emily; Graham, Jeffrey D.; Bedard, Chloe; Rodriguez, Christine; Kriellaars, Dean; Cairney, John
ABSTRACT: Purpose : The purpose of this study was to examine the convergent validity of the PLAYfun tool, a physical literacy-based measure of movement competence, by examining its association with objectively measured physical activity in a sample of children and youth. Method : Participants included 110 children between the ages of seven to 14 years attending a stratified random sample of 27 afterschool programs across the province of Ontario, Canada. The PLAYfun tool was administered to the participants on one occasion at their afterschool program and then they were asked to wear a pedometer for seven consecutive days to measure their physical activity levels. A series of multiple linear regression models were used to examine the association between PLAYfun scores and physical activity, while controlling for age, sex, and time of year (season) in which the data were collected. Results : On its own, the PLAYfun average score accounted for close to 13% of the variance in physical activity, R = .36, R 2  = .13, p < .001. The PLAYfun average score was also a significant independent predictor of physical activity, b ( SE ) = 145.98 (53.46), p < .01, when controlling for age, sex, and season in which the data were collected, R 2   = .30, F (4, 105) = 11.04, p < .001. Conclusion : Results from the present study indicate that the PLAYfun tool is a significant predictor of objectively measured physical activity, supporting the convergent validity of the tool.